Perception and risk tolerance of family farming managers - Duarte, Daura Helena Jales Dantas; Morais , Eulita de Souza; Siqueira, Elisabete Stradiotto; Nobre, Fábio Chaves; Nobre, Liana Holanda Nepomuceno (Seven Editora, 2024)
Objective: to analyze the relationships between the constructs of perception and tolerance, perceived by rural property managers. Theoretical framework: it is based on the literature through family farming and risk tolerance and uncertainties in agriculture. Method: A survey was carried out with 137 farmers. This is a quantitative study of a described nature. The data were collected through a questionnaire and reveal that the behavior of the interviewees is restricted to actions that do not put them in situations of financial risk. Results and conclusion: In the analysis of the means of the risk behavior factor, the results revealed that risk perception precedes risk tolerance, and the relationship between the constructs is of an inverse order, in which managers perceive more risk in a situation in which they have the least tendency to incur risks. In this context, the greater the perceived risk, the less chances the manager will have of carrying out the deal. The findings allowed us to broaden the understanding of the relationships between risk constructs within the decision-making process. In general, family farming managers show signs of the need to manage finances more efficiently and in most cases seek to improve these practices. Implications of the research: the implications of this study for the management of family farming show that managers perceive risk situations, and are unwilling to take this risk (risk tolerance). Originality/value: broadens the understanding of the tolerance to risk linked to the financial of families that live from family farming. DOI:https://doi.org/10.56238/sevened2024.023-028